Celebrating Interfaith Rituals to Build Togetherness Between Children in Elementary Schools - Yenuri, Ali Ahmad; Futaqi, Sauqi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to describe and interpret forms of interreligious rituals in primary schools. Researchers also look at children's religious expressions in practicing interreligious rituals and their contribution as learning resources in building a sense of togetherness in schools. This study uses a qualitative-phenomenological approach with data collection interviews, observations, and documentation. The results showed that children's religious rituals were taught in and outside the classroom. They practice with teachers of the same religion in class, but outside the classroom, they practice with students of other religions as spectators. Therefore, religious rituals that can be communicated socially are celebrated. Interreligious rituals do not make children and parents experience theological fear but can become a source of learning to recognize and respect other religious rituals. The ritual expression is an expression of harmony and togetherness because they can cooperate in celebrating their respective religious rituals.